2017
DOI: 10.3899/jrheum.161589
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Evidence of Gut-driven Systemic Inflammation in Juvenile Idiopathic Arthritis

Abstract: Objective Accumulating evidence links juvenile idiopathic arthritis (JIA) to non-host factors such as gut microbes. We hypothesize that children with new-onset JIA have increased intestinal bacterial translocation and circulating LPS. Methods We studied systemic treatment-naive JIA patients (poly-articular JIA, n=22, oligo-articular JIA, n=31 and spondyloarthropathies, n=16), patients with established inflammatory bowel disease and arthritis (IBD-RA, n=11), and 34 healthy controls. We determined circulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 46 publications
3
19
0
Order By: Relevance
“…In these pilot studies, we foud that 12/61 patients with lupus exceeded the level in any of the tested control subjects (Mann-Whitney, p=0.03) (figure 1G). Furthermore, patients with lupus also displayed raised serum soluble CD14 (Welch test, p=0.0002) and raised α1-acid glycoprotein levels (Welch test, p<0.0001) (figure 1H, I), which in other conditions have been attributed to gut bacterial translocation 28 29. Taken together, these findings suggest that patients with lupus may at times experience impaired gut barrier function, which potentially may enable commensals, or their components, to escape the intestinal lumen.…”
Section: Resultsmentioning
confidence: 88%
“…In these pilot studies, we foud that 12/61 patients with lupus exceeded the level in any of the tested control subjects (Mann-Whitney, p=0.03) (figure 1G). Furthermore, patients with lupus also displayed raised serum soluble CD14 (Welch test, p=0.0002) and raised α1-acid glycoprotein levels (Welch test, p<0.0001) (figure 1H, I), which in other conditions have been attributed to gut bacterial translocation 28 29. Taken together, these findings suggest that patients with lupus may at times experience impaired gut barrier function, which potentially may enable commensals, or their components, to escape the intestinal lumen.…”
Section: Resultsmentioning
confidence: 88%
“…82 By demonstrating the presence of significantly higher levels of circulating gut bacterial products in subjects with juvenile idiopathic arthritis, Fotis et al reinforced the concept that the intestine is a source of immune stimulation in arthritis. 83 Consistent with this hypothesis, Ciccia et al demonstrated increased zonulin expression, damaged intestinal mucosal barrier as well as gut vascular barrier in patients with ankylosing spondylitis. 84 Furthermore, they hypothesized that modulation of monocyte behavior by these bacterial products and zonulin may be the mechanism underlying the disease development.…”
Section: Diseases Linked To Intestinal Barrier Dysfunction and Effectmentioning
confidence: 84%
“…Stratification by clinical and serological phenotypes , demography and habits is qualitative, on disease activity measures quantitative 50–57. Stratification on sex, race, socioeconomic status,58–62 access to medical care, medication choice and adherence,63 willingness to participate in clinical trials, doctor–patient interactions,64 patient preferences and perceptions,65 lifestyle choices,66 67 physician choices,68–71 environmental triggers,72–76 poverty,77 social disparities,78 and life events,79 smoking80 and the gut pathobiont81 all affect manifestations and outcomes in ways that dictate who participates in a study on SLE and in ways that cannot be examined in animal models 82. Stratification on gene expression , quantitative, predicts risk and possibly phenotype83–93; SLE-like illnesses (the autoinflammatory diseases),94 Aicardi-Goutières syndrome,95 96 Canale-Smith syndrome97 and SLE associated with immunodeficiency98 suggest mechanisms for primary illness, and for phenotype diversity.…”
Section: Stratificationmentioning
confidence: 99%